The changing landscape of youth work : theory and practice for an evolving field - Pozzoboni, Kristen; Kirshner, Benjamin (Adolescence and education., 2016)
The purpose of this book is to compile and publicize the best current thinking about training and professional development for youth workers. School age youth spend far more of their time outside of school than inside of school. The United States boasts a rich and vibrant ecosystem of Out-of-School Time programs and funders, ranging from grassroots neighborhood centers to national Boys and Girls Clubs. The research community, too, has produced some scientific consensus about defining features of high quality youth development settings and the importance of after-school and informal programs for youth. But we know far less about the people who provide support, guidance, and mentoring to youth in these settings. What do youth workers do? What kinds of training, certification, and job security do they have?Unlike K-12 classroom teaching, a profession with longstanding - if contested - legitimacy and recognition, "youth work" does not call forth familiar imagery or cultural narratives. Ask someone what a youth worker does and they are just as likely to think you are talking about a young person working at her first job as they are to think you mean a young adult who works with youth. This absence of shared archetypes or mental models is matched by a shortage of policies or professional associations that clearly define youth work and assume responsibility for training and preparation. This is a problem because the functions performed by youth workers outside of school are critical for positive youth development, especially in our current context governed by widening income inequality. The US has seen a decline in social mobility and an increase in income inequality and racial segregation. This places a greater premium on the role of OST programs in supporting access and equity to learning opportunities for children, particularly for those growing up in neighborhoods of concentrated poverty.Fortunately, in the past decade there has been an emergence of research and policy arguments about the importance of naming, defining, and attending to the profession of youth work. A report released in 2013 by the DC Children and Youth Investment Corporation suggests employment opportunities for youth workers are growing faster than the national average; and as the workforce increases, so will efforts to professionalize it through specialized training and credentials. Our purpose in this volume is to build on that momentum by bringing together the best scholarship and policy ideas - coming from in and outside of higher education - about conceptions of youth work and optimal types of preparation and professional development.